Vekst og overlevelse for larver og yngel av atlantiske torskebestander, komparative studier i posesystemer - van der Meeren, Terje (Havforskningsinstituttet, 1995)
To evaluate genetic differences in survival and growth potential under similar environmental and feeding conditions, cod (Gadus morhua L.) larvae from different stocks (Northeast Arctic cod, coastal cod from western Norway, and Balsfjord cod) were reared in 5.2 m3 plastic bag enclosures. In the enclosures, genetically marked coastal cod larvae made it possible to rear larvae from the different stocks together in one enclosure. The enclosures were floating in a saltwater basin used for production of zooplankton. Nauplii, juveniles and adult stages of copepods were collected from the basin and fed to the larval groups according to a theoretical energy model. The different experiments were terminated between day 36 and 48 posthatch. Total numbers and individual larval weights were measured, and samples for stock identification by electrophoresis were taken. In general, larval survival and growth were very high among the 39 single enclosures runned during the project. The results indicate stock-specific difference in growth capability under the given environmental conditions and feeding regimes. Growth rates for Northeast Arctic cod larvae were consistently lower than for coastal cod. No clear stock-specific difference in survival potential was evident. Growth and survival were also investigated under different light conditions, corresponding to the light regimes which the larvae from the two stocks experience in nature. Light regime did not affect the better growth capabilities showed by coastal cod, but use of an artificial light source (light bulbs) reduced both growth and survival significantly. Furthermore, in the larval population of Northeast Arctic cod only, artificial light caused reduced growth rates, leading to a bimodal weight distribution at experiment termination.NORSK SAMMENDRAG:Torskelarver fra ulike bestander (skrei, kysttorsk fra Vestlandet og Balsfjordtorsk) ble drettet opp i 5,2m3 plastposer under like fysiske og ernæringmessige betingelser. Bruk av kysttorsklarver med en genetisk markør gjorde det mulig å drette opp larvene fra de ulike bestandene i en og samme pose. Posene var plassert i et sjøvannsbasseng som ble benyttet for produksjon av zooplankton. Copepodnauplier, copepoditter og copepoder ble samlet inn fra bassenget og fôret larvene i henhold til en teoretisk energimodell. De ulike forsøkene ble avsluttet mellom dag 36 og 48 etter klekking. Antall, vekt og genetisk bestandstilhørighet ble bestemt. Generelt ble god overlevelse og vekst observert i de 39 enkeltposene som forsøkene omfattet i løpet av prosjektet. Resultatene tyder på en bestandsavhengig forskjell i vekstevne under de gitte oppdrettsforhold. Vekstraten hos skreilarvene var signifikant larvere enn hos kysttorsklarvene. Det ble ikke funnet et tilsvarende klart mønster for overlevelse. Vekst og overlevelse ble også undersøkt under forskjellige lysregimer som samsvarer med det skrei og kysttorsklarver erfarer i naturen. Lysregime hadde ingen virkning på den observerte forskjellen i vekstrate, men bruk av en kunstig lyskilde (lysrør) i stedet for naturlig lys reduserte vekst og overlevelse uavhengig av bestandstilhørighet. Videre førte kunstig lys til at en del av skreilarvepopulasjonen vokste langsommere, noe som gav en bimodal vektfordeling ved forsøksslutt.